Komodo dragons are not ecological analogs of apex mammalian predators. Issue 4 (3rd February 2020) - Jessop, Tim S.; Ariefiandy, Achmad; Forsyth, David M.; Purwandana, Deni; White, Craig R.; Benu, Yunias Jackson; Madsen, Thomas; Harlow, Henry J.; Letnic, Mike
Abstract: Apex predators can have substantial and complex ecological roles in ecosystems. However, differences in species‐specific traits, population densities, and interspecific interactions are likely to determine the strength of apex predators' roles. Here we report complementary studies examining how interactions between predator per capita metabolic rate and population density influenced the biomass, population energy use, and ecological effects of apex predators on their large mammalian prey. We first investigated how large mammal prey resources and field metabolic rates of terrestrial apex predators, comprising large mammals and the Komodo dragon ( Varanus komodoensis ), influenced their biomass densities and population energy use requirements. We next evaluated whether Komodo dragons, like apex mammalian predators, exerted top‐down regulation of their large mammal prey. Comparison of results from field studies demonstrates that Komodo dragons attain mean population biomass densities that are 5.75−231.82 times higher than that of apex mammalian predator species and their guilds in Africa, Asia, and North America. The high biomass of Komodo dragons resulted in 1.96−108.12 times greater population energy use than that of apex mammalian predators. Nevertheless, substantial temporal and spatial variation in Komodo dragon population energy use did not regulate the population growth rates of either of two large mammal prey species, rusa deer ( Rusa timorensis ) and wild pig ( Sus scrofa ). We suggest that multiple processes weaken the capacity of Komodo dragons to regulate large mammal prey populations. For example, a low per capita metabolic rate requiring an infrequent and inactive hunting strategy (including scavenging), would minimize lethal and nonlethal impacts on prey populations. We conclude that Komodo dragons differ in their predatory role from, including not being the ecological analogs of, apex mammalian predators.